2006
DOI: 10.1002/ca.20226
|View full text |Cite
|
Sign up to set email alerts
|

The gross anatomy of the extrathoracic course of the intercostobrachial nerve

Abstract: Recent reports emphasize the importance of preserving the intercostobrachial nerve (ICBN) during surgical procedures (i.e., mastectomy, axillary clearance). However, a limited number of scientific reports explore the surgical anatomy of this nerve. We dissected 100 adult human formalin-fixed cadavers (200 axillae). In all the cadavers the ICBN was present with variant contributions from intercostal nerves T1, T2, T3, and T4. The arrangements of the ICBN were typed as I through VIII. The components of Type I (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
67
0
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 13 publications
2
67
0
7
Order By: Relevance
“…In some conditions, the ICBN combines with the lateral cutaneous branch of the first and/or intercostal nerve (Loukas et al, 2006). Our study found that a single trunk of the ICBN that originated from the second intercostal nerve accounted for 75.6% (118/156) of cases, but in 21.8% of cases, the ICBN originated from the first intercostal nerve, the first and second intercostal nerves, the second and third intercostal nerves, or the first, second, and third intercostal nerves.…”
Section: Discussionmentioning
confidence: 99%
“…In some conditions, the ICBN combines with the lateral cutaneous branch of the first and/or intercostal nerve (Loukas et al, 2006). Our study found that a single trunk of the ICBN that originated from the second intercostal nerve accounted for 75.6% (118/156) of cases, but in 21.8% of cases, the ICBN originated from the first intercostal nerve, the first and second intercostal nerves, the second and third intercostal nerves, or the first, second, and third intercostal nerves.…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, 23 pacientes (62,2%) com DA-NS não apresentaram dor e 10 pacientes (27,05%) não apresentaram déficit sensorial. É possível que nestas pacientes a inervação seja mantida devido às variações na anatomia e distribuição do suprimento nervoso da axila e braço 16 . Com a evolução de cirurgias mais radicais para as cirurgias conservadoras, observou-se que dor crônica também ocorre após setorectomia ou quadrantectomia.…”
Section: Discussionunclassified
“…As our dissection of the ICBN aimed to reproduce the surgical conditions of a transfer to the LCMN, the dissection was not prolonged distally toward the arm and was interrupted when a sufficient length of the ICBN was achieved to reach the LCMN and the proposed technique could be applied. Thus, some of the communication of the ICBN with other nerves of the upper limb were probably not visualized and described, as they were in other studies 11,12,14,30 . Despite the limitations, our study confirmed the anatomical feasibility of a direct coaptation, without interposition grafts and without tension, between the ICBN and the LCMN through dissection of an average extension of 54 ± 10 mm from the origin of donor nerve to the coaptation point to the recipient nerve.…”
Section: Discussionmentioning
confidence: 84%
“…Loukas et al 11 described that the ICBN is anatomically constant, and Maycock et al 25 reinforced the idea that the ICBN is responsible for the cutaneous innervation of the axilla region and the medial and posterior aspects of the arm. Thus, this nerve has an area of cortical representation closer to the hand area than the SCN and the ICNs 26 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation